Shouting in the Library: the Radical Voices season at the University of London’s Senate House Library - Caroline Kimbell (Insights: The UKSG Journal, 2017)
From its inception, the University of London has defined itself in opposition to the classical elitism of pre-Victorian academia. Described by Dickens as ‘the people’s university’, its founding principles emphasized social inclusion, the betterment of the individual through education and the contributions to the national economy of innovation, invention and hard work. The university’s central research library at Senate House holds a unique corpus of 18th- to 20th-century radical political collections, among which is the library of the Family Welfare Association, with its ground-breaking campaigning around disability, prison conditions, public health and child poverty. Senate House Library and the Institute of Historical Research hosted a season of public and online exhibitions, ‘radical walks’, talks, film screenings and sound installations between January and March 2017, which saw contemporary radical thinkers Ken Loach and Ron Heisler connecting with their predecessors, through their book and manuscript legacies, to tell accessible stories and encourage new audiences into dialogue with ‘the people’s university’. This article explores the successes, challenges and lessons learned from the programme, while the events themselves brought new audiences in to encounter the history of protest and reform in a notoriously inaccessible space.